Comparison of Lidocaine-triamcinolone Injection with and without Magnesium Sulfate in Ankle Joint Osteoarthritis - Sabaghzadeh, Amir; Mosaffa, Faramarz; Hosseini, Behnam; Rezaeian, AhmadReza (Archives of Men’s Health, 2023)
Background: Currently available pharmacological therapies for osteoarthritis mainly target palliation of pain and include analgesics, intra-articular therapy, and topical treatment. We aimed to evaluate the effect of the concomitant use of magnesium sulfate in addition to a combination of triamcinolone and lidocaine. Methods: To evaluate the changes in pain factor levels, sixty patients with ankle osteoarthritis were randomly divided into two control (Triamcinolone + Lidocaine) and intervention (Triamcinolone + Lidocaine + Magnesium sulfate) groups (n= 30, each group). In both groups, patients were injected with 80 mg triamcinolone and 0.5 cc of 2% lidocaine, while in the intervention group, 500 mg of magnesium sulfate was added to the injecting solution, and in the control group, an equivalent volume of 0.9% normal saline was added to the injecting solution. Patients were monitored after one week and one month and each completed the visual analog scale (VAS) and American Orthopedic Foot and Ankle Society (AOFAS) pain score questionnaires in addition to their demographic characteristics. The results were evaluated based on the design of the questionnaire and data were analyzed employing SPSS software, version 21, and using independent ttest. Results: AOFAS and VAS scores were significantly different between the intervention and control groups within one week after treatment (p value= 0.018) but AOFAS and VAS scores after one month were not significantly different. Conclusion: Using magnesium sulfate was effective in controlling the pain caused by ankle osteoarthritis at short intervals.